Pentahelix Model in the Development of Pecaringan Hill Tourism in Jombang Regency - Vani Laila; Diana Hertati (Borong Newinera Publisher, 2024)
In order to improve the tourism sector, the Jarak Village Government seeks to develop Pecaringan Hill Tourism by collaborating on the pentahelix model. However, it is not yet known the extent of involvement of each actor related to the development of Pecaringan Hill Tourism. The purpose of this study is to determine the involvement of each actor in maintaining their synergy to optimize the collaboration of the pentahelix model in Pecaringan Hill Tourism Development. The research method used in this study is a descriptive research method with a qualitative approach. With data analysis techniques using interactive data developed by Miles & Huberman. The focus of the research uses the pentahelix model theory from Irawan, (2021), namely Academics, Business, Community, Government, and Media. The results showed that the implementation of this pentahelix model collaboration has been realized, the involvement of each actor in maintaining their synergy to optimize the pentahelix model collaboration in Pecaringan Hill Tourism Development is considered to be quite stable, but still has not had a significant impact on the development of Pecaringan Hill Tourism. This is evidenced by the number of visitors on Pecaringan Hill Tourism which is still relatively small every year. Thus, it can be implied that the pentahelix model in the development of Pecaringan Hill Tourism has been carried out, it can be concluded that the collaboration of the pentahelix model in the development of Pecaringan Hill Tourism in Jombang Regency has been realized and carried out with the continuity of actors that are quite stable.